A Conceptual Framework for Increasing Innovation through Improved Selection of Specialized Professionals. Issue 1 (2nd January 2019) - Jeffcoat, Keith L.; Eveleigh, Timothy J.; Tanju, Bereket
Abstract: Engineering managers involved in product development and manufacturing are responsible for proposing and developing ideas and concepts that will benefit new or existing products and processes. Improved methods are required to identify, prioritize, and integrate the opinions, ideas, and concepts proposed by specialized professionals (SP) or subject matter experts into their existing product development and process improvement. Identifying the optimal SPs and utilizing these for concept generation efforts can lead engineering management working in the new product/technology development space toward an improved idea/concept generation, increased innovation, and ultimately, superior products and processes. Methods for locating, assessing, and ranking SPs vary with every organization, but in general, systematic methods and processes are not considered, which results in the reliance on internal or limited external experts. This study aims to directly impact the engineering managers by bridging the gap between the traditional business management and core engineering management for providing guidance and improving the way in which the practicing engineering managers deal with new product development and management of technology. This experimental study is derived using a real-world engineering problem, which is faced in the field of engineering management, and the results support the implementation of a conceptual SP-focused framework that provides an increased quality of the concept generation outputs, improved preparation for future product development stages, and reduced costs.